KETOPROFEN: APPLICATION AND DOSAGE FORMS - A. V. Belyatskaya; I. I. Krasnyuk (Jr.); I. I. Krasnyuk; T. E. Machikina; Yu. A. Korosteleva; O. I. Stepanova; I. M. Kashlikova; Y. V. Skovpen; A. N. Vorob'yov (Разработка и регистрация лекарственных средств, 2019)
Ketoprofen is a medicinal substance that has not lost its relevance in modern medicine and pharmacy. The article describes the aspects of its application. The prospects of creating new dosage forms containing ketoprofen are considered. The possibility of creating effervescent dosage forms containing solid dispersions of ketoprofen is described.